(untitled) (Research, Society and Development, 2021)
Introduction/Objective: This retrospective cross-sectional cohort study analyzed the extravasation index of antineoplastic therapy agents, demographic and clinical data. Methods: Seventy-six patients were evaluated in the period between 2017-2019. The project was approved by the Research Ethics Committee of a Brazilian Foundation. Results: In 72 months, 105,890 applications were administered, of which the incidence rate of extravasation of antineoplastic agents was 0.071%. Patients (N=311) selected for this study had a mean age of 55.42 years and a median age of 57. The most frequent diagnoses were breast cancer (11.66%), ovarian cancer (10%), colon cancer (8.33), rectal cancer (8.33) and uterine cancer (8.33%). The main variables that presented a significant impact with p <0.05 were ECOG Scale of Performance Status, ethnicity, age (risk ratio of 3% plus for each year of life), cancer staging, lymphadenectomy, use of venous catheter, forearm puncture, use of alkylating and alkaloids agents in peripheral venous access, and patients with tumor located in the pelvis using alkylating agents. Conclusion: The findings reinforce the need for further studies, since it was not possible to compare results with some variables that demonstrated a significant increase in the risk for the event.